Molecular epidemiology and current management of Infectious Spleen and Kidney Necrosis Virus (ISKNV) infection in Ghanaian cultured tilapia - Ayiku, A.N.A.; Adelani, A.A.; Duodu, S.; et al. (Aquaculture, 2024)
Infectious Spleen and Kidney Necrosis Virus (ISKNV) is globally gaining more attention, due to its highly sig nificant economic impact on the aquaculture industry. In late 2018, unusually high levels of mortality (60–90%) was reported in some intensive tilapia cage culture systems on the Eastern bank of Lake Volta in Ghana. This resulted in the fold-up of several small and medium scale farms. Preliminary investigations confirmed the involvement of ISKNV, a viral pathogen noted for fatal systemic infections in many fish species. As a follow-up on the outbreak situation, and post-mass vaccination of affected fish farms, the need to investigate further the molecular epidemiology and phylogeography of the virus across Lake Volta became paramount. A multiplexed PCR assay to detect the virus and MinION™ nanopore sequencing of the Major Capsid Protein (MCP) were performed to investigate the presence and genotype of ISKNV in tilapia collected from 30 randomly selected farms at various geographical locations. ISKNV was found to be widely distributed across the lake and detected in 80% of farms with a reported average daily mortality of 40%. Fry and juvenile fish were the most affected, and approximately 50% of fish that tested positive were asymptomatic. These apparently healthy fish are likely contributors of virus transmission across farms. Phylogenetic analysis of the MCP revealed that all 35 isolates from 14 different farms distributed across the lake clustered with ISKNV clade I with 100% homology to isolates from the 2019 outbreak strain. Vaccination and heat-shock treatment; the two main specific interventions currently employed to control the viral pathogen have not achieved much success, and ISKNV remains a threat to the growth of the aquaculture industry in Ghana. The outcome of this study can be useful in improving fish health management and biosecurity policies in the aquaculture industry.
Research Article
Keywords: Aquaculture; Tilapia; Vaccine